An overview of the history of learning theory. (31st January 2018) - Illeris, Knud
Abstract: This article is an account of the history of learning theory as the author has come to know and interpret it by dealing with this subject for almost half a century during which he has also himself gradually developed the broad understanding of human learning which is presented in his wellknown books on "How We Learn" and a lot of other books and writings.